A new hierarchically porous Cu-MOF composited with rGO as an efficient hybrid supercapacitor electrode material. (November 2021) - Singh, Mayank K.; Gupta, Anoop K.; Krishnan, Sarathkumar; Guha, Nikita; Marimuthu, Senthilkumaran; Rai, Dhirendra K.
Highlights: A new biporous Cu-MOF was synthesized by under solvothermal conditions. The Cu-MOF/rGO composite was synthesized using simple ultrasonication technique. The Cu-MOF/rGO composite shows a hybrid capacitive behavior. The composite shows a specific capacitance of 366.6 Fg −1 at 1 Ag −1 current density. The symmetrical supercapacitor device shows a high energy density of 14.66 Whkg −1 . Abstract: Exploring new materials for efficient energy storage is imperative to derive uninterrupted energy supply from non-conventional sustainable sources. The present paper reports on the synthesis of a new Cu-MOF (HMRL-1), involving the reaction of a tetracarboxylic linker and Cu 2+ salt under solvothermal conditions. Using a simple ultrasonication approach, the as-synthesized MOF has been further used to fabricate a composite with reduced graphene oxide (rGO) ( R ). The resulting composite (HMRL-1/R) has been explored as a binder-free supercapacitor electrode material for deriving enhanced charge storage capacity. The supercapacitor performance of the composite material has been investigated by cyclic voltammetry (CV), galvanostatic charge-discharge (GCD), and electrochemical impedance spectroscopy (EIS). The electrochemical investigations reveal that HMRL-1/R composite exhibits hybrid capacitive features with a specific capacitance (CS ) of 366.6 Fg −1 at 1 Ag −1 and excellent cyclic stability and performance retention, which is much higher than that of pristine HMRL-1 and R due to their synergistic effect. All the findings suggest that as-prepared material is a promising candidate for an electrode material in supercapacitor applications. Graphical abstract: Image, graphical abstract